Hepatitis C virus core or NS3/4A protein expression preconditions hepatocytes against oxidative stress and endoplasmic reticulum stress. (1st January 2019) - Ríos-Ocampo, W. Alfredo; Daemen, Toos; Buist-Homan, Manon; Faber, Klaas Nico; Navas, María-Cristina; Moshage, Han
ABSTRACT: Objectives: The occurrence of oxidative stress and endoplasmic reticulum (ER) stress in hepatitis C virus (HCV) infection has been demonstrated and play an important role in liver injury. During viral infection, hepatocytes must handle not only the replication of the virus, but also inflammatory signals generating oxidative stress and damage. Although several mechanisms exist to overcome cellular stress, little attention has been given to the adaptive response of hepatocytes during exposure to multiple noxious triggers. Methods: In the present study, Huh-7 cells and hepatocytes expressing HCV Core or NS3/4A proteins, both inducers of oxidative and ER stress, were additionally challenged with the superoxide anion generator menadione to mimic external oxidative stress. The production of reactive oxygen species (ROS) as well as the response to oxidative stress and ER stress were investigated. Results: We demonstrate that hepatocytes diminish oxidative stress through a reduction in ROS production, ER-stress markers ( HSPA5 [GRP78], sXBP1 ) and apoptosis (caspase-3 activity) despite external oxidative stress. Interestingly, the level of the autophagy substrate protein p62 was downregulated together with HCV Core degradation, suggesting that hepatocytes can overcome excess oxidative stress through autophagic degradation of one of the stressors, thereby increasing cell survival. Duscussion: In conclusion, hepatocytes exposed to direct and indirect oxidative stress inducers are able to cope with cellular stress associated with viral hepatitis and thus promote cell survival.